2011
DOI: 10.1007/s00216-011-5145-6
|View full text |Cite
|
Sign up to set email alerts
|

Elemental ratio determinations and compound-independent calibration using microsecond pulsed glow discharge time-of-flight mass spectrometry

Abstract: A new prototype based on a microsecond pulsed glow discharge ion source coupled to a time-of-flight mass spectrometer was recently designed, constructed and analytically evaluated in our laboratory for simultaneous collection of elemental and molecular information, and as a gas-chromatographic detector of compounds of environmental concern. To investigate further the analytical capabilities of such a new setup, its capability for the determination of element ratios in volatile organic halogenated compounds has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An alternative approach for compound-independent calibrations is recently proposed based on the use of an internal standard. 9 This approach is demonstrated in Fig. 5b where Cl − peak area for each analyte in Fig.…”
Section: Linearity and Limits Of Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach for compound-independent calibrations is recently proposed based on the use of an internal standard. 9 This approach is demonstrated in Fig. 5b where Cl − peak area for each analyte in Fig.…”
Section: Linearity and Limits Of Detectionmentioning
confidence: 99%
“…Elemental mass spectrometry (MS), on the other hand, offers a distinct advantage because of its compound-independent calibration based on intrinsic and added elemental tags. 9,10 This advantage is tremendously useful when compound-specific standards are not readily available, a scenario often encountered in characterization of environmental and metabolic transformation products. By incorporating a separation step prior to elemental detection, absolute concentrations of elements related to each compound are measured, in turn yielding molecular concentrations based on molecular formulas.…”
Section: Introductionmentioning
confidence: 99%
“…However, signal maxima (I max ) for heavier Pb isotopes occur closer to the load coil than I max for lighter Pb isotopes, the reverse of the ICPMS elemental observations. These mass dependent distributions predict that the radial dispersion and axial I max locations for 203 Tl and 205 Tl isotopes should occur interspersed with the values for simultaneously measured Pb isotopes. Instead however, their values are appropriate for masses greater than 208 Pb, indicating that the observed profiles are not the product of a single stage mass dependent process and that other element properties also effect the distributions.…”
Section: ■ Atomic Emission Spectrometrymentioning
confidence: 93%
“…Pulsed rf GD-TOF-MS also proved to yield interesting results as a gas-chromatographic detector for compounds of environmental concern, for the simultaneous collection of elemental and molecular information. 203 A compound-independent calibration was carried out, and the intensity ratios (analyte to internal standard) were linear with the corresponding ratio of the concentrations. Moreover, the detection limits were improved by 1 order of magnitude compared to using external calibration.…”
Section: ■ Atomic Emission Spectrometrymentioning
confidence: 99%
“…Sanz-Medel and co-workers have reported 120 on a new ms pulsed GD ion source coupled to a TOF mass spectrometer that was recently designed, constructed and evaluated for the simultaneous collection of elemental and molecular information, and as a GC detector for compounds of environmental relevance, such as volatile organic halogenated compounds. It was shown that the intensity ratios for Cl and Br could be correlated to the number of atoms in a molecule of the selected compound and, furthermore, that compound-independent calibrations were possible.…”
Section: Developments In Instrumentationmentioning
confidence: 99%